PENGARUH EDUKASI KESEHATAN DENGAN E-BOOKLET TERHADAP BREASTFEEDING SELF EFFICACY DAN MATERNAL DEPRESSIVE SYMPTOM DI MASA PANDEMI COVID 19 - Siti Rochana; Septi Tri Aksari; Titi Alfiani (UPT PPM Sekolah Tinggi Ilmu Kesehatan Al Irsyad Al Islamiyyah Cilacap, 2022)
Post partum experience physical and psychological changes that can be affected by the COVID-19 pandemic. Mothers who cannot adapt to the critical postpartum period can experience psychological disorders that also affect breast milk production. The design used was quasi experimental with a pre and post test approach with control group design. The sampling technique used was consecutive sampling with a sample size of 60. The instruments used were the Breastfeeding Self Efficacy Scale-Short Form (BSES-SF) and the Edinburgh Postnatal Depression Scale (EPDS). The statistical tests used were the Mann Whitney test and the Wicoxon Signed Rank Test. The results of the analysis showed that health education with e-booklets had a significant effect on breastfeeding self-efficacy with a value of =0.039 (<0.05) and an average increase of 7.16 which was higher than the control group. Meanwhile, on the EPDS score, the group with the provision of health education with e-booklets decreased by 1.5 points on average and the results of the analysis showed a significant effect with a value of =0.002 (<0.05). In conclusion, the provision of health education with e-booklets has an effect on breastfeeding self-efficacy and EPDS scores. Suggestions for breastfeeding mothers to read e-booklets to increase mother's self-efficacy and reduce EPDS scores. Keywords: Education, Breastfeeding self efficacy, Maternal depressive symptom, Covid-19